Spatial Cognition IX International Conference, Spatial Cognition 2014, Bremen, Germany, September 15-19, 2014. Proceedings - Freksa, Christian; Nebel, Bernhard; Hegarty, Mary.; Barkowsky, Thomas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the thoroughly refereed proceedings of the 9th International Conference on Spatial Cognition, Spatial Cognition 2014, held in Bremen, Germany, in September 2014. The 27 revised full papers presented in this book were carefully selected and reviewed from 53 submissions. The papers are organized in topical sections on spatial memory; language and communication; wayfinding and navigation; computational models; diagrams and maps; technical approaches; and spatial ability.
Spatial memory -- Language and communication -- Wayfinding and navigation -- Computational models -- Diagrams and maps -- Technical approaches -- Spatial ability.
Keywords: Computer science; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Computer simulation; Computer graphics; Computer Science; Simulation and Modeling; Computer Imaging, Vision, Pattern Recognition and Graphics; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Electronic books